Scleromitrion diffusum (Willd.) R. J. Wang Inhibits Gastric Cancer via ERBB2/ERBB3/PI3K/AKT Pathway - Ye, Wei; Zhao, Qiu; Li, Peng; Zhou, Tong (Turkish Journal of Gastroenterology, 2024)
Background/Aims: This study aimed to evaluate the anticarcinogenic potential of Scleromitrion diffusum (Willd.) R. J. Wang (SD) extracts in vitro, along with exploring the underlying compatibility mechanisms. Materials and Methods: Scleromitrion diffusum (Willd.) R. J. Wang extract was prepared and gastric cancer (GC) cells were treated to detect the half maximal inhibitory concentration (IC50)/proliferation and migration/invasion by MTS method and transwell assay. The compatibility mechanisms of SD were analyzed by systems pharmacology strategy, combined with cellular experimental validation. Results: Scleromitrion diffusum (Willd.) R. J. Wang extract showed inhibitory ability on the proliferation of the GC cell lines dose- and time-dependently. A total of 3 active ingredients are involved in anti-gastric cancer effects of SD, based on the top 50 pathways. The “herb-composition-target-pathway” network showed the multi-target and multi-pathway characteristics of SD. There were 52 related targets shared by SD and GC. The cellular experiments supported that SD significantly reduced ERBB2 and ERBB3 expression levels in GC cells. The overexpression of ERBB2 or ERBB3 partially offset the anti-tumor effects of SD. Conclusion: Scleromitrion diffusum (Willd.) R. J. Wang inhibited gastric cancer growth and metastasis in vitro, which may be related to the inhibition of the ERBB2/ERBB3/PI3K/AKT pathway. Cite this article as: Ye W, Zhao Q, Li P, Zhou T. Scleromitrion diffusum (willd.) R. J. wang inhibits gastric cancer via ERBB2/ERBB3/ PI3K/AKT pathway. Turk J Gastroenterol. 2024;35(11):831-838.